Asymptomatic Right Ventricular Hypoplasia in Twin Siblings: A Normal Variant or Cause of Early Mortality? - Amna Qasim; Soham Dasgupta; Ashraf M. Aly (Case Reports in Pediatrics)
Right ventricular (RV) hypoplasia may develop secondary to pulmonary or tricuspid valve atresia. These patients are usually symptomatic early in life and need prompt intervention. Isolated RV hypoplasia is a rare congenital heart disease. We report a case of 23-year-old twins who have been monitored for the last 14 years for isolated right ventricular hypoplasia. ECHO and MRI studies showed a small, heavily trabeculated, nonapex-forming RV and mild tricuspid valve insufficiency. The girl has a patent foramen ovale (PFO). Otherwise, the cardiac anatomy and function was normal. They have both been completely asymptomatic from the cardiac standpoint. The family history is remarkable for death of father at the age of 30 years with autopsy suggestive of a hypoplastic RV. The paternal uncle also died at the age of 46 years, and his son has an unidentified congenital heart disease. The family history appears to suggest an autosomal dominant pattern of inheritance with variable expressivity. However, the chromosome microarray analysis of the twins did not identify any variations of clinical significance.